Information literacy implications for the quality of academic and research work - Špiranec, Sonja (Array, 2006)
Building the citizens' information literacy capacity to access and use information and knowledge in today's information society and knowledge-based economy is a key to the further progress of the social, cultural and economic development of countries. This publication is intended to inform and inspire policy makers, educators and the LIS community to prepare and implement information literacy strategies in the countries of Central and Suouth-Eastern Europe, which are lagging behind in achieving the knowledge and skills necessary to use ever- increasing information and knowledge resources.